2017
DOI: 10.4317/medoral.22133
|View full text |Cite
|
Sign up to set email alerts
|

Exposed necrotic bone in 183 patients with bisphosphonate-related osteonecrosis of the jaw: Associated clinical characteristics

Abstract: BackgroundThe main objective of our study was to identify oral symptoms and signs most likely to be associated with the exposure of necrotic bone in bisphosphonate-related osteonecrosis of the jaw (BRONJ).Material and MethodsThe study group consisted of 183 patients with BRONJ. We recorded data on the underlying disease, bisphosphonate used, location of osteonecrosis, symptoms, pain, fistula development, suppuration, infection, exposed necrotic bone, and BRONJ stage.ResultsThe mean age of the patients was 68.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…In the current case, the patient had a history of bisphosphonate medication for 22 months before dental implant. A study by Bagan et al showed a direct association between the use of intravenous bisphosphonate therapy and the development of MRONJ after dental implant placement, but this risk is lower from a simple tooth extraction in these patients. Some studies recommended patients taking IV BPs for more than 3 years with no local risk factors and those taking BPs for <3 years together with steroid therapy to take a 3‐to‐6‐month drug holiday prior to dental surgery, and in this patient, physician recommended a 6‐month drug holiday before dental implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, the patient had a history of bisphosphonate medication for 22 months before dental implant. A study by Bagan et al showed a direct association between the use of intravenous bisphosphonate therapy and the development of MRONJ after dental implant placement, but this risk is lower from a simple tooth extraction in these patients. Some studies recommended patients taking IV BPs for more than 3 years with no local risk factors and those taking BPs for <3 years together with steroid therapy to take a 3‐to‐6‐month drug holiday prior to dental surgery, and in this patient, physician recommended a 6‐month drug holiday before dental implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathogen is Actinomyces israeli, but the presence of A. viscosus, A. naeslundi, A. odontolyticus is also observed [9]. Any damage to the mucous membrane in mouth allows the bacteria to penetrate into deeper tissues and cause inflammation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the general condition of the patient also affects the occurrence of Actinomycosis -people with coexisting systemic diseases that disrupt the function of the immune system are more predisposed. Clinical symptoms of Actinomycosis are leatherlike infiltration of subcutaneous tissue with forming fistulas, from which characteristic yellowgreen clumps are filtered [10,11] Infection can be spread to the bone, which in the case of cervical-facial Actinomycosis, is most often the mandible [9]. In this case, on radiological images an osteolytic defect can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations